Ab initio relativistic treatment of the a3Π−X1Σ+, a′3Σ+−X1Σ+ and A1Π−X1Σ+ systems of the CO molecule. (March 2021) - Mosyagin, N.S.; Oleynichenko, A.V.; Zaitsevskii, A.; Kudrin, A.V.; Pazyuk, E.A.; Stolyarov, A.V.
Highlights: Spin-forbidden a − X, a ′ − X and spin-allowed A − X transition moments of CO were obtained using fully relativistic approach. The radiative lifetimes of a 3 Π and A 1 Π states were evaluated as functions of vibrational and rotational quantum numbers. The lifetimes derived for the a 3 Π state are in a near perfect agreement with their best experimental counterparts. The intercombination transition probabilities were found to be almost strictly proportional to the squared fine structure constant α . Abstract: The spin-forbidden a 3 Π − X 1 Σ +, a ′ 3 Σ + − X 1 Σ + and spin-allowed A 1 Π − X 1 Σ + electronic transitions dipole moments of carbon monoxide have been ab initio studied in the framework of multi-reference Fock space coupled cluster method combined with the finite-field approach and the generalized relativistic pseudo-potential model for the effective introducing the relativity in all-electron correlation treatment. Radiative lifetimes, τ i ( v ′, J ′ ), of the upper i ∈ [ a 3 Π, A 1 Π ] states were evaluated as a function of vibrational, v ′, and rotational, J ′, quantum numbers. The τ a -values derived for the triplet a 3 Π 1 ( 0, 1 ) and a 3 Π 2 ( 0, 2 ) states at the highest level of computation were found to be 2.59 and 142 ms, which are near perfect agreement with their best experimental counterparts (J. J. Gilijamse, et al., J. Chem. Phys., 127, 221102 (2007)). The intercombination a − X, a ′ − X transition probabilities were numerically proved to be proportional to α 2, where α = e 2 / ℏ c is the fine structure constant.